Trends in consumption of energy and total sugars from sugar-sweetened beverages in the United States among youth and adults, NHANES 2003–March 2020 and August 2021–August 2023 - Mary M. Murphy; Maribeth M. Anderson; Kelly A. Higgins (Nutrition and Health, 2026)
Background Sugar-sweetened beverages (SSB) are a key source of energy and sugars in the American diet. Aim This assessment examined trends in SSB and sugar-sweetened carbonated soft drink (ssCSD) consumption. Methods Intake estimates were generated using NHANES 2003–2020 and August 2021-August 2023 and temporal trends were examined using linear and logistic regression. Summary The percentage of individuals ≥2 years consuming SSB or ssCSD declined significantly from 2003 to 2023. The percentage of youth consuming SSB or ssCSD dropped from 2003 to 2023 (76%–44% and 56% to 22%, respectively), as did the percentage of adults consuming SSB or ssCSD (52%–32% and 42%–22%, respectively). Per capita energy intake from SSB or ssCSD declined among youth (−135 and −96 kcal/day, respectively) and adults (−89 and −75 kcal/day, respectively). The downward trends in SSB or ssCSD consumption among the US population suggest trends consistent with dietary recommendations.